Application of the Analytical Hierarchy Process (AHP) Method in Supporting Decision-Making Regarding Drug Abuse Factors - Rewan Jayadi; Herry Suprajitno; Miswanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
Drugs are an abbreviation for narcotics and dangerous drugs, whether natural, synthetic, or semi-synthetic. The use and spread of illegal drugs worldwide shows a sharp increase, spreading and affecting all countries and people of all religions, and has caused many fatalities. The purpose of this study is to apply the Analytic Hierarchy Process (AHP) method in evaluating risk factors and analyzing the performance of each criterion against drug abuse areas. This data primarily comes from the Bengkulu Province National Narcotics Agency. The consistency test results for each criterion and alternative in the AHP method show consistent values of less than 0.1, indicating that the data used meet the consistency standards required by Saaty for the AHP method. The results of the analysis of preferences for risk factors show that family factors have the highest weight, meaning the role of family is very important, followed by peer group factors, personality, community environment, economic and psychosocial factors, drug availability, anxiety and depression, and school environment. Keywords: AHP, drug abuse, MCDM, risk factors, Bengkulu Province